Suicidal Ideation pada Remaja Yogyakarta Ditinjau dari Pemaknaan Hidup - Windi Cahyaningrum; Zahro Varisna Rohmadani (EduInovasi: Journal of Basic Educational Studies, 2025)
Suicidal ideation is a significant mental health issue that has gained considerable attention, especially among adolescents. The psychological, social, and emotional changes that occur during adolescence often increase their vulnerability to mental health disorders. Various factors, both internal and external, can influence the emergence of suicidal ideation, including life meaning, which can affect an individual’s tendency toward suicidal thoughts. Life meaning refers to how individuals assign meaning to their lives, which is believed to function as a protective mechanism against feelings of hopelessness and the tendency to end one’s life. This study aims to examine the relationship between these two variables in adolescents. A quantitative approach with a correlational design and simple linear regression analysis was used in this study. The variables of suicidal ideation and life meaning were measured using a Likert scale. The sample consisted of 100 adolescents aged 12-21 years in Yogyakarta, with data collected through questionnaires distributed via Google Form and paper-based formats. Data analysis was conducted using Spearman’s test with SPSS for Windows version 26. The results indicated a significant negative relationship between suicidal ideation and life meaning, with a correlation coefficient of -0.548 and a significance value of ρ = 0.000 (ρ < 0.05).